Screening of wild and synthetic wheat genotypes for resistance against corn leaf aphid, Rhopalosiphum maidis (Fitch) - Pritam Kumari; Poonam Jasrotia (Journal of Cereal Research, 2023)
Among different aphid species attacking wheat crop, corn leaf aphid R. maidis (Fitch) severely threaten wheat production. A total of twenty eight genotypes of wheat including Aegilops tauschii, synthetic wheat and Ae. ovata were screened for two years against corn leaf aphid. In the first year of screening (2021-22), one highly resistant, nine resistant (R) and 14 moderately resistant (MR) and four susceptible wheat accessions were identified. Further screening done in second year (2022-23), identified one highly resistant, 13 resistant, 12 moderately resistant and two susceptible wheat accessions against corn leaf aphid. The majority of wheat accessions were found moderately resistant or resistant to corn leaf aphid. Overall, the two years of screening identified one highly resistant (Ae tauschii 3744b), five moderately resistant (Ae tauschii 33 and 3744a; synthetic SYN4 and SYN47; Ae. ovata 87), six resistant ( Ae tauschii 9807, 13764, 3769 and 13762; synthetic SYN55, and Ae. ovata 2) and two susceptible accessions (Ae tauschii 3757 and synthetic SYN21) against corn leaf aphid.